High School Students Perceptions of Problem-Based Learning (PBL) Integrated with Anthropogenic Phenomena: An Analysis of Engagement and Motivation - Dewi, Evie Sylviana; Lestari, Nurita Apridiana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The importance of student engagement and motivation in the physics learning process at the high school level, which has often been perceived as a difficult subject and less relevant to real life. Through the integration of anthropogenic phenomena, learning is expected to become more contextual and foster awareness of environmental issues. This study aims to determine students' perceptions of physics learning activities using the Problem-Based Learning (PBL) model integrated with anthropogenic phenomena. The research was conducted at the high school level using a quantitative descriptive approach. The respondents consisted of 108 tenth-grade students who had participated in physics learning using this model. The research instrument was a validated questionnaire. Data were analyzed using a Likert scale and presented in percentage form. The results of the study indicate that students' perceptions of physics learning using the integrated anthropogenic PBL model are in the good and very positive categories. This is demonstrated by the percentage of engagement aspects exceeding 80% and the motivation aspects reaching 86%. Overall, both aspects scored 61% or higher, indicating that the application of this model is effective in enhancing student engagement and motivation in learning. These findings are expected to serve as a reference for teachers in developing contextual physics learning and contribute as supporting literature for future research.